Improve operational performance by simulating the Holonic manufacturing system A case study at the rubber product plant in Al-Najaf Al-Ashraf - الجنابي, ياسر نجم; حسن, شفاء بلاسم (Journal of Economics and Administrative Sciences, 2020)
The research aims to improve operational performance through the application of the Holonic Manufacturing System (HMS) in the rubber products factory in Najaf. The problem was diagnosed with the weakness of the manufacturing system in the factory to meet customers' demands on time within the available resources of machines and workers, which led to time delays of Processing and delivery, increased costs, and reduced flexibility in the factory, A case study methodology used to identify the reality of the manufacturing system and the actual operational performance in the factory. The simulation was used to represent the proposed (HMS) by using (Excel 2010) based on the actual data and calculate the operational performance measures and compare them with the actual operational performance measures in the factory. The results confirmed that the application of the (HMS) in the factory leads to a reduction in the delay time, delivery times, and production costs due to the participation of the machines and workers in the resources and workers Holons